2020
DOI: 10.52279/jlss.02.01.1019
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits and Academic Performance

Abstract: This study investigates the impact of Big Five personality traits on the academic performance of university students in terms of their CGPA by using 20 item short Mini-IPIP Five-Factor personality test developed by Donnellan, Oswald, Baird, and Lucas (2006). The purpose of using this short measures test is to come up with a generalized and effective quick personality test for predicting academic performance (in terms of CGPA) in students. The study was conducted on undergraduate college students at Forman Chri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Some statistical limitations, such as range restriction, are yet to be addressed by GPA. 37 Besides GPA, researchers use different operational definitions for academic performance, such as single subject performance, 38 cognitive skills, 38 self-growth, 10 and study habits. 12 These terms are most commonly considered alongside academic performance using GPA in various operational definitions in academic work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some statistical limitations, such as range restriction, are yet to be addressed by GPA. 37 Besides GPA, researchers use different operational definitions for academic performance, such as single subject performance, 38 cognitive skills, 38 self-growth, 10 and study habits. 12 These terms are most commonly considered alongside academic performance using GPA in various operational definitions in academic work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result contradicts previous findings ( Giluk and Postlethwaite, 2015 ) that postulated a relationship between the personality trait of extraversion and the tendency to cheat. One possible explanation for this result may be extraversion’s personality trait characteristics, their high motivation to learn, and their proactive personality ( John et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammadov (2022) conducted a meta-analysis finding relationships between openness to experience, extraversion, and agreeableness with learning achievement. While no significant correlations between neuroticism and extraversion with learning achievement were found by John et al (2020). De Feyter et al (2012 found positive effects for neuroticism on learning achievement when self-efficacy is high.…”
Section: Personalitymentioning
confidence: 92%